1996
DOI: 10.18474/0749-8004-31.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Diamondback Moth (Lepidoptera: Plutellidae) Contamination of Cabbage Transplants and the Potential for Insecticide Resistance Problems

Abstract: Samples collected from 1989 to 1992 document that the diamondback moth, Plutella xylostella (L.) was introduced into New York in early spring on cabbage, Brassica oleracea capitata (L.), transplants grown in the southern United States. During 1989, transplant shipments from five transplant companies in Florida, Georgia and Maryland were sampled for P. xylostella. In 1989, average seasonal infestations per transplant company ranged from 1.3 to 3.5 P. xylostella per 100 transplants. During June, when the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…Locations either had persistently high or low resistance levels over several years, likely to be related to continued selection for resistance because of pyrethroid applications. Although P. xylostella may be transported on vegetable transplants leading to resistance problems in other localities (Shelton et al, 1996), no obvious patterns attributable to this phenomenon were observed in this study, though the origin of vegetable seedlings at particular locations was not traced in detail.…”
Section: Patterns Of Resistance In Populationscontrasting
confidence: 59%
“…Locations either had persistently high or low resistance levels over several years, likely to be related to continued selection for resistance because of pyrethroid applications. Although P. xylostella may be transported on vegetable transplants leading to resistance problems in other localities (Shelton et al, 1996), no obvious patterns attributable to this phenomenon were observed in this study, though the origin of vegetable seedlings at particular locations was not traced in detail.…”
Section: Patterns Of Resistance In Populationscontrasting
confidence: 59%
“…This can be easily explained for P. xylostella as it is an excellent migrator ( Chu , 1986) but is more difficult to explain for the guild. One would have to suppose a massive introduction of these species during the transport of cabbage plants ( Shelton et al., 1996) or possibly that they were already present on other hosts. This appears to be the case for T. diatreae which originally also attacked other Lepidoptera, principally Noctuidae but is a pupal parasitoid of P. xylostella in Jamaica ( Alam , 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The sources of these outbreaks have not been identified, but reports, especially from the northern hemisphere, indicate that DBM is a migratory species and periodically disperses over long distances (Chu, 1986;Talekar & Shelton, 1993). Also, larvae can be brought into a cropping region on imported vegetables (Voice & Chapman, 2000) or contaminated seedlings (Shelton et al, 1996). Studies of population-genetic structure have potential to help in determining gene flow patterns, and hence dispersal and movement patterns, of DBM across Australia and in other regions of the world.…”
Section: Introductionmentioning
confidence: 99%